Plaque burden in HIV-infected patients is associated with serum intestinal microbiota-generated trimethylamine. (20th February 2015) - Srinivasa, Suman; Fitch, Kathleen V.; Lo, Janet; Kadar, Hanane; Knight, Rachel; Wong, Kimberly; Abbara, Suhny; Gauguier, Dominique; Capeau, Jacqueline; Boccara, Franck; Grinspoon, Steven K.
Abstract : Objective: Some intestinal microbiota-generated metabolites of phosphatidylcholine are recognized to be proatherogenic. As the HIV population is vulnerable to cardiovascular disease and can develop intestinal dysbiosis associated with systemic inflammation, we investigated the novel relationship between microbiota-derived metabolites of phosphatidylcholine and coronary atherosclerosis in HIV. Design/Methods: One hundred and fifty-five HIV-infected and 67 non-HIV-infected individuals without known history of cardiovascular disease were previously recruited to assess coronary plaque by computed tomography angiography. In the current study, we evaluate whether serum choline, trimethylamine (TMA), or trimethylamine- N -oxide (TMAO) levels are associated with plaque features. Results: Young, asymptomatic HIV-infected patients (age 47 ± 7 years) demonstrated significantly higher prevalence of plaque (53 vs. 35%, P  = 0.01) and number of total plaque segments (1.8 ± 2.5 vs. 1.2 ± 2.2, P  = 0.03) when compared with well matched noninfected individuals with similar comorbidities. TMA was significantly associated with calcium score ( r  = 0.22, P  = 0.006), number of total ( r  = 0.20, P  = 0.02) and calcified ( r  = 0.18, P  = 0.03) plaque segments, and calcium plaque volume ( r  = 0.19, P  = 0.02) and mass ( r  = 0.22, P  = 0.009) in the HIV cohort only. In multivariate modeling among HIV-infected patients, TMA remained significantly associated with calcium score ( P  = 0.008), number of total ( P  = 0.005) and calcified ( P  = 0.02) plaque segments, and calcium plaque volume ( P  = 0.01) and mass ( P  = 0.007), independent of Framingham risk score. In contrast, there was no association of TMAO to coronary plaque features in either cohort. Conclusion: A link between TMA and atherosclerosis has not previously been established. The current study suggests that TMA may be a nontraditional risk factor related to the number of plaque segments and severity of calcified plaque burden in HIV. Abstract : Supplemental Digital Content is available in the text